Quantity and quality of memory and guesses in pattern recall of complex soccer scenarios - Li, Jie; Lu, Hanshuang; Yang, Zipeng; Li, Qi; Zhou, Qian; Che, Xiang; Zhang, Yu (Taylor & Francis, 2025)
In soccer, players need to keep in mind the locations of the ball and numerous teammates and opponents in complex scenarios. This study aimed to examine both the quantity and quality of players’ memory and guess in pattern recall for complex soccer scenarios. We developed an adapted pattern recall task in which participants were required to reproduce player locations in complex scenarios through two stages, allowing for the separation of memory from guesses and the subsequent analysis of accurate memory and false memory. The results showed that soccer athletes could maintain the locations of about eight players, along with the ball, in accurate memory for complex soccer scenarios, showing a greater quantity of accurate memory than non-athletes, whereas the precision of memory did not differ between the two groups. On the other hand, non-athletes falsely memorised the locations of a larger number of attacking players and tended to make more guesses about the locations of defending players than soccer athletes. Moreover, soccer athletes displayed superior precision when guessing player locations compared to non-athletes. These findings suggest that soccer athletes leverage their knowledge to enhance the chunking of individual players to be maintained in short-term memory and facilitate the inferences about player locations exceeding the limit of short-term memory, providing them with an advantage in both memory quantity and guess quality in complex soccer scenarios.